2018
DOI: 10.1080/19420889.2018.1451719
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetics disrupt brain development via actions on the mTOR pathway

Abstract: Experiments conducted in non-human primates have recently provided new evidence supporting a longstanding concern that exposure to general anesthesia during late intrauterine life or early childhood can cause lasting cognitive deficits through harmful effects on brain development. The mammalian target of rapamycin (mTOR) signaling system plays a key role in both normal brain development and in a wide range of developmental disorders that are characterized by cognitive deficits. Intriguingly, our recently publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…However, mTOR has not been extensively studied in this context, and the evidence linking it to anesthetic toxicity is mixed [25].…”
Section: Introductionmentioning
confidence: 99%
“…However, mTOR has not been extensively studied in this context, and the evidence linking it to anesthetic toxicity is mixed [25].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, DMGs altered by maternal FA de ciency were enriched distinctively in mTOR signaling pathway, Notch signaling pathway, neurotrophin signaling pathway and protein processing in ER. The mTOR signaling plays vital roles in dendritic formation and axon guidance during normal brain development [28], and aberrant mTOR signaling has been implicated in neurodevelopment disorders that characterized by cognitive de cits, such as tuberous sclerosis and fragile X syndrome [29]. Notch signaling maintains the neural stem cells pool during brain development [30], regulates cortical cell-type differentiation in an orderly progression [31], and interacts with Reelin signaling regulating cortical neuronal migration [32].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which anesthetics could act on the developing brain to have a lasting impact remains unclear, although numerous candidate targets, many of which are not mutually exclusive, have been proposed (Kang, et al 2017;Mintz, et al 2013;Xu, et al 2018a;Xu, et al 2018b). The GABA receptor is an intriguing target, as activity at this receptor is one of the few things that is common to many general anesthetics agents (Franks and Lieb 1994;Jones, et al 1992;Kapfhammer, et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The potential mechanism by which a limited developmental exposure to anesthetic or sedatives could have a lasting effect on cognitive function remains unclear, but most data point to one of two possibilities, which are not mutually exclusive. Anesthetics may have direct cytotoxic effects in developing brain cells (Jackson, et al 2016;Yang and Wei 2017) and/or they may alter the formation of brain circuitry (Xu, et al 2018a). In previous work, we have found that anesthetic agents have the potential to interfere with the development of connectivity in the brain by disrupting axon guidance (Mintz, et al 2013), the process by which developing axons grow towards the appropriate dendritic targets to establish appropriate circuitry (Blanquie and Bradke 2018;Russell and Bashaw 2018).…”
Section: Introductionmentioning
confidence: 99%